Pengembangan LKPD Berbasis Model Pembelajaran Problem Based Learning dengan Konteks Literasi Numerasi Peserta Didik Kelas X SMK N 1 Palembayan - Riska Novita Sari; Isnaniah Isnaniah; Rusdi Rusdi; Ulva Rahmi (Departement of Mathematics Education, 2023)
This research is motivated by the problems identified in class X SMK N 1 Palembayan, namely a poor learning environment, the LKPD used does not contain the context of numeracy literacy and is not yet based on problem-based learning. student. Thus making it difficult for students to understand the mathematical concepts they are learning. This study aims to create student worksheets based on problem-based learning models with a valid, practical and effective numeracy context for class X students of SMK N 1 Palembayan. This research is a research and development (R&D) type using the Sugiyono development model. This LKPD was validated by four validators and then corrected according to the validator's suggestions. Practical test results from student answer questionnaires and performance tests from student learning outcomes. Based on the development research conducted, it is known that the validity level of LKPD is 80.91% which is in the valid criteria, the practicality level is 81.33%, it is in the very practical criteria and the effectiveness level is 83% it is in the very effective criteria. It can be concluded that the LKPD Mathematics Based on the Problem Based Learning Model with the Context of Numerical Literacy for Class X SMK N 1 Palembayan which was developed is valid, practical, and effective.